2011
DOI: 10.1111/j.1365-2966.2011.18380.x
|View full text |Cite
|
Sign up to set email alerts
|

4098 galaxy clusters to z∼ 0.6 in the Sloan Digital Sky Survey equatorial Stripe 82

Abstract: We present a catalogue of 4098 photometrically selected galaxy clusters with a median redshift 〈z〉= 0.32 in the 270 deg2‘Stripe 82’ region of the Sloan Digital Sky Survey (SDSS), covering the celestial equator in the Southern Galactic Cap (−50° < α < 59°, |δ| ≤ 125). Owing to the multi‐epoch SDSS coverage of this region, the ugriz photometry is ∼2 mag deeper than single scans within the main SDSS footprint. We exploit this to detect clusters of galaxies using an algorithm that searches for statistically signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 32 publications
0
38
1
Order By: Relevance
“…7. MS galaxies from previous studies are shown by the green stars (Daddi et al 2010b;Geach et al 2011;Magdis et al 2012;Bauermeister et al 2013;Tacconi et al 2013), and it can be seen that the field correlation around the locus of MS galaxies is tighter here than in the SFR-L CO[1−0] plane, Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7. MS galaxies from previous studies are shown by the green stars (Daddi et al 2010b;Geach et al 2011;Magdis et al 2012;Bauermeister et al 2013;Tacconi et al 2013), and it can be seen that the field correlation around the locus of MS galaxies is tighter here than in the SFR-L CO[1−0] plane, Fig. 7.…”
Section: Discussionmentioning
confidence: 99%
“…(Sargent et al 2014). A sample of MS galaxies between 0<z<3 are shown by the green stars for comparison (Daddi et al 2010b;Geach et al 2011;Magdis et al 2012;Bauermeister et al 2013;Tacconi et al 2013). The errors on the average SFRs include a 0.17 dex systematic uncertainty, as well as the measurement errors.…”
Section: Star-formation Efficienciesmentioning
confidence: 99%
“…Of these clusters, 16 259 BCGs (62 percent) have spectroscopic redshifts from SDSS data, as given in their catalogue. Geach et al (2011) presented a cluster catalogue of 4098 objects identified in the SDSS Stripe 82 region based on statistical galaxy overdensities. The redshift of these systems ranges from 0.04 to 0.8.…”
Section: Optical Cluster Surveysmentioning
confidence: 99%
“…For example, Geach et al (2011) detected 4098 clusters up to redshift z ∼ 0.6 by applying an algorithm that searches for statistically significant overdensities in Tables A.1, C.1, and C.2 are also available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/594/A32 a Voronoi tesselation of the projected sky. Durret et al (2015) applied the AMACFI cluster finder (based on photometric redshifts) in the same region and detected 3663 candidate clusters.…”
Section: Introductionmentioning
confidence: 99%
“…This method is not all that different from ours, and it would be very interesting to apply it to the CFHTLS Wide data, to compare the cluster candidates obtained by their method and by ours. A comparable method has been applied to the SDSS Stripe 82 by Geach et al (2011) to search for clusters up to z ∼ 0.6. The paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%